THE INFLUENCE OF VOTER BEHAVIOR ON THE GENERAL ELECTION OF REGIONAL HEADS IN THE RIAU ISLANDS PROVINCE - Melina, Bonita; Ariyanto, Hepy Hefri; Nainggolan, Ferdinand (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
This study aims to examine the factors influencing voter decision-making among first-time voters in the 2024 regional head elections in the Riau Islands Province. Employing a quantitative research design, the study utilizes survey methods through questionnaires distributed to 100 respondents selected using purposive sampling. The research investigates five key variables: Attitude Toward the Behavior, Subjective Norms, Perceived Behavioral Control, Social Media Political Marketing Activity, and Negative Political Advertising. Data collection was conducted using a Likert-scale questionnaire, and the data were analyzed using SPSS version 25. Hypothesis testing was carried out through both partial and simultaneous regression analyses. The results indicate that all five independent variables significantly affect the voting decisions of first-time voters, suggesting that individual beliefs, social expectations, perceived ease of performing the behavior, online political engagement, and exposure to negative campaigning all play substantial roles in shaping voter behavior. These findings underscore the importance of strategic communication and ethical political engagement tailored to the youth demographic. For policymakers and campaign teams, understanding these determinants can support more inclusive and effective approaches to encourage political participation among young voters in regional elections, particularly in geographically dispersed areas like the Riau Islands.